2014
DOI: 10.5114/aoms.2014.42584
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone therapy in opioid overdose patients: intranasal or intravenous? A randomized clinical trial

Abstract: IntroductionThis study was designed to compare the effects of intranasal (IN) and intravenous (IV) administration of naloxone in patients who had overdosed on opioids.Material and methodsThis randomized clinical trial study was conducted in the Department of Poisoning Emergencies at Noor and Ali Asghar (PBUH) University Hospital. One hundred opioid overdose patients were assigned by random allocation software into two study groups (n = 50). Both groups received 0.4 mg naloxone: one group IN and the other IV. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 33 publications
(26 reference statements)
1
26
0
2
Order By: Relevance
“…For example, Barton et al (2005) compared naloxone IV (1-2 mg) or IN (2 mg) for opioid overdose in humans, and found that both routes were equally effective in reversing overdose within 3 minutes. Other studies investigating IN versus IM or IV NLX for opioid overdose reached similar conclusions (e.g., Kerr et al, 2009;Sabzghabaee et al, 2014). Although the experimental design in the current study did not allow us to assess the onset of action, which was a noted limitation, the finding that NLX given IN and IV was equipotent in reversing antinociception is consistent with these single-dose studies in humans.…”
Section: Discussionsupporting
confidence: 78%
“…For example, Barton et al (2005) compared naloxone IV (1-2 mg) or IN (2 mg) for opioid overdose in humans, and found that both routes were equally effective in reversing overdose within 3 minutes. Other studies investigating IN versus IM or IV NLX for opioid overdose reached similar conclusions (e.g., Kerr et al, 2009;Sabzghabaee et al, 2014). Although the experimental design in the current study did not allow us to assess the onset of action, which was a noted limitation, the finding that NLX given IN and IV was equipotent in reversing antinociception is consistent with these single-dose studies in humans.…”
Section: Discussionsupporting
confidence: 78%
“…administration of naloxone reversing opioid overdose: at least 327 overdose reversals using nasal naloxone kits were reported in the Massachusetts ‐based take‐home naloxone scheme . In ambulance and hospital‐based trials, the time from dose administration to clinical response often took longer for nasal administration compared to injectable routes . However, for the comparison of i.n.…”
Section: Resultsmentioning
confidence: 99%
“…naloxone administration in healthy volunteers or patients with suspected opioid overdose. Eighteen records matched our search criteria (see Table and Fig. ).…”
Section: Methodsmentioning
confidence: 99%
“…When administered intramuscularly or intravenously, naloxone has a rapid effect on respiratory depression, within 1 to 2minutes of administration. Although initial investigations of intranasal naloxone did not support its effectiveness, a recent randomized clinical trial of an intranasal reformulation found that it was as effective as intravenous naloxone in reversing opioid overdose-induced respiratory and CNS depression (11). Intranasal naloxone has the advantage of reducing the risks of needle-stick injury and transmission of blood-borne illnesses, as well as the potential for peer administration of naloxone (12).…”
Section: Prescription Opioid Overdosementioning
confidence: 99%